Efficient genetic transformation and CRISPR/Cas9‐mediated genome editing in Lemna aequinoctialis. Issue 11 (3rd May 2019) - Liu, Yu; Wang, Yu; Xu, Shuqing; Tang, Xianfeng; Zhao, Jinshan; Yu, Changjiang; He, Guo; Xu, Hua; Wang, Shumin; Tang, Yali; Fu, Chunxiang; Ma, Yubin; et al.
Summary: The fast growth, ease of metabolic labelling and potential for feedstock and biofuels production make duckweeds not only an attractive model system for understanding plant biology, but also a potential future crop. However, current duckweed research is constrained by the lack of efficient genetic manipulation tools. Here, we report a case study on genome editing in a duckweed species, Lemna aequinoctialis, using a fast and efficient transformation and CRISPR/Cas9 tool. By optimizing currently available transformation protocols, we reduced the duration time of Agrobacterium‐ mediated transformation to 5–6 weeks with a success rate of over 94%. Based on the optimized transformation protocol, we generated 15 (14.3% success rate) biallelic LaPDS mutants that showed albino phenotype using a CRISPR/Cas9 system. Investigations on CRISPR/Cas9‐mediated mutation spectrum among mutated L. aequinoctialis showed that most of mutations were short insertions and deletions. This study presents the first example of CRISPR/Cas9‐mediated genome editing in duckweeds, which will open new research avenues in using duckweeds for both basic and applied research.